Life destiny of erythrocyte in high altitude erythrocytosis: mechanisms underlying the progression from physiological (moderate) to pathological (excessive) high-altitude erythrocytosis - Zhou, Xiaoying; Bao, Quanwei; Cui, Yu; Li, Xiaoxu; Yang, Chengzhong; Yang, Yidong; Gao, Yuqi; Chen, Dewei; Huang, Jian (Frontiers in Genetics, 2025)
High-altitude polycythemia (HAPC) represents a pathological escalation of the physiological erythrocytosis induced by chronic hypoxia exposure. While moderate erythroid expansion enhances oxygen delivery, HAPC manifests as hematologic disorder characterized by hemoglobin thresholds (≥21 g/dL males; ≥19 g/dL females) and multi-organ complications including microcirculatory thrombosis, right ventricular hypertrophy, and uric acid dysmetabolism. This review critically evaluates the continuum between adaptive and maladaptive polycythemia through multiscale analysis of erythrocyte biology. We integrate genomic predisposition patterns, bone marrow erythroid kinetic studies, and peripheral erythrocyte pathophenotypes revealed by multi-omics profiling (iron-redox proteome, hypoxia-metabolome crosstalk). Current diagnostic limitations are highlighted, particularly the oversimplification of hemoglobin cutoffs that neglect transitional dynamics in erythrocyte turnover. By reconstructing the erythroid life cycle—from hypoxia-sensitive progenitor commitment to senescent cell clearance—we propose a phase transition model where cumulative epigenetic-metabolic derangements overcome homeostatic buffers, triggering pathological erythroid amplification. These insights reframe HAPC as a systems biology failure of erythroid adaptation, informing predictive biomarkers and targeted interventions to preserve hematological homeostasis in hypoxic environments.